A problem solving environment for image-based computational hemodynamics - Schaap, Jorrit A. (2013)
We introduce a complete problem solving environment designed for pulsatile flows in 3D complex geometries, especially arteries. Three-dimensional images from arteries, obtained from e.g. Magnetic Resonance Imaging, are segmented to obtain a geometrical description of the arteries of interest. This segmented artery is prepared for blood flow simulations in a 3D editing tool, allowing to define in- and outlets, to filter and crop part of the artery, to add certain structures ( e.g. a by-pass, or stents ), and to generate computational meshes as input to the blood flow simulators. Using dedicated fluid flow solvers the time dependent blood flow in the artery during one systole is computed. The resulting flow, pressure and shear stress fields are then analyzed using a number of visualization techniques. The whole environment can be operated from a desktop virtual reality system, and is embedded in a Grid computing environment.